Diagnóstico situacional da população idosa adscrita a uma unidade de atenção primária à saúde do município de Fortaleza - Marsylle, Janaína Moreno Nogueira (2020)
The accelerated growth of the elderly population in Brazil has caused alterations in its epidemiological and demographical characteristics, requiring changing the whole context of health service toward that clientele. The Elderly Person’s Health Handbook was the guiding tool to the study and the chosen and analysed variables present in its internal content were the attributes to establish the situational diagnosis of the elderly population adjoined in the range area of the Health Team 429. It’s a trans-sectional, descriptive and field study of a predominantly quantitative character, carried out in Fortaleza, at the Executive Bureau of Regional IV in Primary Attention to Health Unit, comprehending 132 elders, including bedridden and circumscribed at home. The data collection was gathered through structured interview, subsidized by tools which include socio-demographical characterization, of health and the Vulnerable Elder Identification Protocol (VES-13). A descriptive analysis of the data was performed and, in order to evaluate the behaviour between two variables, Fischer’s statistic test was applied. There was no prevalence of vulnerability (64,6%) among the elders of the Community and the variables that showed a positive relation with the VES-13 score were: the feminization of the ageing (62,9%), the predominance of elders in the micro area 2 and 4 (65,4%), with a major marital status of married or living with a partner (40,2%), patients with diabetes (p-rate < 0,001), with a concomitant use of 5 or more medicines (p-rate 0,015) and the elders who manifest other frequent health conditions (57,6%) or already presented some health condition (50,8%). The self-perception in health evaluated through Vulnerable Elder Identification Protocol (VES-13) was considered bad by most of the elderly participants (58,3%). The construction of the situational diagnosis of the Family Health 429 team’s responsibility field will contribute to the creation of a care line toward the elders in the local management as to the organization of actions in the field of health performed by the health team that participated to the survey with the elders in its territory.